Constructivist instructional design (C-ID) : foundations, models, and examples - Willis, Jerry, 1942- (Qualitative research methods in education and educational technology, 2009)
This book is about emerging models of design that are just beginning to be used by ID types. They are based on constructivist and chaos (non-linear systems or "soft systems") theory.This book provides constructivist instructional design (C-ID) theorists with an opportunity to present an extended version of their design model. After an introductory chapter on the history of instructional design models, and a chapter on the guiding principles of C-ID, the creators of six different C-ID models introduce and explain their models. A final chapter compares the models, discusses the future of C-ID models, and discusses the ways constructivist designers and scholars can interact with, and work with, instructional technologists who use different paradigms.